2020
DOI: 10.1021/acs.est.9b07476
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanisms of Iodine–Ammonia Clusters in Polluted Coastal Areas Unveiled by Thermodynamics and Kinetic Simulations

Abstract: It has been revealed that iodine species play important roles in atmospheric new particle formations (NPFs) in pristine coastal areas. However, it is unclear whether other atmospheric species, such as NH3, for which the levels in coastal areas of China are >2.5 × 1010 molecules·cm–3 are involved in the NPFs of iodine species, although NH3 has been proved to promote particle formation of H2SO4. Via high-level quantum chemical calculations and atmospheric cluster dynamic code simulations, this study unveiled new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…Our present nitrate CIMS experiments indicate that this competition likely occurs between I 2 O 5 –I x O y clustering and slow hydrolysis by the water dimer. 32 The concentration of I x O y in our flow tube is high (∼10 10 to 10 12 cm –3 ) compared to atmospheric conditions (10 7 to 10 9 cm –3 ). For low water concentrations, I 2 O 5 and HIO 3 are mainly removed by clustering with I x O y , and low concentrations of HIO 3 and I 2 O y ·HIO 3 clusters exist, which may be too low to be detectable by PIMS in experiments with the same time scale as in the present ones.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our present nitrate CIMS experiments indicate that this competition likely occurs between I 2 O 5 –I x O y clustering and slow hydrolysis by the water dimer. 32 The concentration of I x O y in our flow tube is high (∼10 10 to 10 12 cm –3 ) compared to atmospheric conditions (10 7 to 10 9 cm –3 ). For low water concentrations, I 2 O 5 and HIO 3 are mainly removed by clustering with I x O y , and low concentrations of HIO 3 and I 2 O y ·HIO 3 clusters exist, which may be too low to be detectable by PIMS in experiments with the same time scale as in the present ones.…”
Section: Discussionmentioning
confidence: 61%
“…Hence, these observations suggest that I 2 O 5 reacts with water to generate HIO 3 . The reaction between I 2 O 5 and H 2 O is precluded by a large barrier in the PES, 30 but recent ab initio calculations at the CCSD(T)//M06-2X/aug-ccpVTZ-PP + ECP28 level 32 indicate that hydrolysis of I 2 O 5 by the water dimer is feasible …”
Section: Discussionmentioning
confidence: 99%
“…15,18 Extensive studies indicate that iodine oxoacids play important roles in NPF in marine regions. 17,[19][20][21][22] In Mace head, a coast in Ireland, NPF events were observed along with a high-concentration of iodic acid (HIO 3 ) and a low-concentration of iodous acid (HIO 2 ), and the nucleation was speculated to proceed by the sequential addition of HIO 3 , followed by intracluster restructuring to I 2 O 5 . 17 Recently, a theoretical study indicated that HIO 3 can self-nucleate in clean coastal regions and the selfnucleation of HIO 3 can also be influenced by sulfuric acid and ammonia in polluted coastal regions.…”
Section: Introductionmentioning
confidence: 99%
“…19 Additionally, a theoretical study has studied the formation mechanism of HIO 3 -ammonia clusters in polluted coastal areas and this new mechanism can well explain the observed cluster formation rates at a coastal site in Zhejiang of China. 20,21 Moreover, a recent experimental study indicates that HIO 3 is the major driver in both nucleation and growth processes of iodine oxoacid particles and remains as the dominant constituent of the freshly formed particles, and HIO 2 plays an important role in neutral nucleation by stabilizing HIO 3 clusters against evaporation. 22 Hence, the participation of HIO 2 in nucleation has caught our concern.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above sulfur precursors, recent experimental and theoretical studies (He et al, 2021;Martí n et al, 2020;Xia et al, 2020;Rong et al, 2020) have also recognized the critical role of iodine compounds in marine NPF process.…”
Section: Introductionmentioning
confidence: 99%